2001
DOI: 10.1097/00000658-200107000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Improving Survival Results After Resection of Hepatocellular Carcinoma: A Prospective Study of 377 Patients Over 10 Years

Abstract: ObjectiveTo investigate whether the survival results after resection of hepatocellular carcinoma (HCC) have improved within the past decade by an analysis of a prospective cohort of patients over a 10-year period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
331
3
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 535 publications
(355 citation statements)
references
References 43 publications
18
331
3
3
Order By: Relevance
“…However, most of these studies included patients with metastatic liver cancer or benign liver tumours who had normal parenchyma in the non-cancerous region of the liver. Transfusion rates and mean blood loss during hepatectomy for patients suffering from HCC, most of whom in East Asian countries have underlying liver disease, are still over 30 per cent and over 1000 ml respectively 2,15,25 .…”
Section: Discussionmentioning
confidence: 99%
“…However, most of these studies included patients with metastatic liver cancer or benign liver tumours who had normal parenchyma in the non-cancerous region of the liver. Transfusion rates and mean blood loss during hepatectomy for patients suffering from HCC, most of whom in East Asian countries have underlying liver disease, are still over 30 per cent and over 1000 ml respectively 2,15,25 .…”
Section: Discussionmentioning
confidence: 99%
“…However, thus far, no randomized trial comparing open and laparoscopic liver resection has been reported. The 5-year survival after resection of HCC is 35-50% in recent large cohort studies [257][258][259]. The long-term survival after hepatic resection depends on tumor characteristics.…”
Section: Liver Resectionmentioning
confidence: 99%
“…In Taiwan, HCC is a leading neoplasm due to the high prevalence of chronic viral hepatitis [3][4][5] . Surgical resection, liver transplantation and local ablation therapy are considered potentially curative therapies for HCC nowadays [6,7] . However, only 9% to 27% of patients are suitable for operation [8,9] .…”
Section: Introductionmentioning
confidence: 99%